Latent Class Models in the Assessment of Education: The Case of Students’ Academic Attainment in Elementary Education in Zacatecas - Muro González, Francisco (Education Policy Analysis Archives, 2008)
Based on an advanced statistical method (Latent Class Analysis), the author jointly examines two crucial factors in the assessment of students? performance in elementary school: School attainment and teacher education ( based on teachers? results in tests taken to earn their teaching credentials). Data from files in the 2001 Archives for the State of Zacatecas, Mexico are used to make this analysis. The author shows that when working with latent class models, one can make a more significant in depth analysis because by virtue of using this method, it is viable to construct suitable clusters and to segment the data files more efficiently in order to find differentiated effects of parameters in the population.